Optimalisasi Pelayanan dan Mutu Rumah Sakit Melalui Rekam Medis Elektronik Yang Efektif : Literature Review - Oksaviyani Alfareza (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
In the ever-growing digital era, hospitals are required to adopt the latest technology, one of which is electronic medical records (RME). RME is a digital patient health data recording system that offers various advantages in improving service quality and hospital operational efficiency. This study aims to examine improving hospital services through the implementation of RME by conducting a literature review. The research uses a literature review method by identifying, selecting and analyzing relevant literature related to the implementation of RME and its impact on improving the quality of hospital services over the last 10 years. Data is analyzed descriptively to find patterns, trends and consistent findings. The results of the literature review show that the implementation of RME can increase the effectiveness of outpatient services, improve the quality of health care, and improve patient safety. RME provides easy access and sharing of patient health information between medical personnel, increased security and privacy of patient data, as well as efficiency in data storage and tracking. However, there are challenges such as large initial investment costs, risk of technical glitches, and resistance from medical personnel to system changes. Implementing RME in hospitals provides many benefits in improving service quality and hospital quality. However, careful planning, support from all parties, and handling of existing challenges and weaknesses are needed to ensure the success of RME implementation.